Tuning CARs: recent advances in modulating chimeric antigen receptor (CAR) T cell activity for improved safety, efficacy, and flexibility - Piotr Celichowski; Marcello Turi; Sandra Charvátová; Dhwani Radhakrishnan; Neda Feizi; Zuzana Chyra; Michal Šimíček; Tomáš Jelínek; Juli Rodriguez Bago; Roman Hájek; Matouš Hrdinka (Journal of Translational Medicine, 2023)
Abstract Cancer immunotherapies utilizing genetically engineered T cells have emerged as powerful personalized therapeutic agents showing dramatic preclinical and clinical results, particularly in hematological malignancies. Ectopically expressed chimeric antigen receptors (CARs) reprogram immune cells to target and eliminate cancer. However, CAR T cell therapy's success depends on the balance between effective anti-tumor activity and minimizing harmful side effects. To improve CAR T cell therapy outcomes and mitigate associated toxicities, scientists from different fields are cooperating in developing next-generation products using the latest molecular cell biology and synthetic biology tools and technologies. The immunotherapy field is rapidly evolving, with new approaches and strategies being reported at a fast pace. This comprehensive literature review aims to provide an up-to-date overview of the latest developments in controlling CAR T cell activity for improved safety, efficacy, and flexibility.